If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -6 = 42 Reorder the terms: -6 + 3p = 42 Solving -6 + 3p = 42 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3p = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 3p = 42 + 6 3p = 42 + 6 Combine like terms: 42 + 6 = 48 3p = 48 Divide each side by '3'. p = 16 Simplifying p = 16
| (5x+6)(5x^2-17x+6)=0 | | 180=2x+15+x | | 180=2x-15+x | | 3+5+6=15+16+72 | | -30x^2-9x+12=0 | | 20-12m=12-15m | | 2ln(7x)=6 | | -18x^2-39x+20=0 | | 9c+3=15c-3 | | 5+2d=7 | | d^12+-4d^2=0 | | 5Y^2-4y-2=0 | | d^12-4d^2=0 | | x^4+1296=0 | | 9m^2-16n^2= | | 2z+z=45 | | 12x+5=10x-3 | | -4x+3=3x-4 | | n^2-3n-80=0 | | 2x-5=c | | abL-m=Lmy-a | | 3y+y=90 | | 3x+8=2x-20 | | x^2+8x+14= | | 9-3x=4x-4 | | 6y-9x=12 | | 5x+7y=o | | 3x-(x-2)=2x-3*(x+1) | | 4x-3*(2x+5)=10x-3-14x | | 4x^2+4x+2=3x^2+x+11 | | 3n+8=32 | | 2x-10+4x+40=90 |